2015
DOI: 10.1021/acs.organomet.5b00495
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Pincer Complexes with an Olefin Backbone

Abstract: Among the large variety of pincer complexes, those with carbon− carbon double bonds in the backbone have received little attention. Here, we report the reactions of complex (PCCP)IrPh (3) and its derivatives with small molecules. Compound 3 readily adds CO to give the 18e adduct (PCCP)IrPhCO (5a), which upon heating undergoes isomerization into the thermodynamically more stable isomer (PCCP)IrCO(Ph) (5b), via reversible loss of CO. Reaction of 5 with hydrogen leads to the formation of saturated carbonyl com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…24 Compound 7 reacts with COE and TBE in benzene solution at room temperature forming deep red solutions of complexes 8 and 9, correspondingly (Scheme 3). 25,26 These experiments show that COE binds much stronger than TBE to compound 7. The signal from 8 agrees very well with the signal of the reaction mixture after catalysis.…”
Section: Isolation Of Intermediatesmentioning
confidence: 95%
“…24 Compound 7 reacts with COE and TBE in benzene solution at room temperature forming deep red solutions of complexes 8 and 9, correspondingly (Scheme 3). 25,26 These experiments show that COE binds much stronger than TBE to compound 7. The signal from 8 agrees very well with the signal of the reaction mixture after catalysis.…”
Section: Isolation Of Intermediatesmentioning
confidence: 95%
“…Reactivity of complex 68 with the olefin backbone and its derivatives towards small molecules such as CO, H 2 , CF 3 COOH, and O 2 has been presented recently, and it was suggested that such complexes were best categorized as olefin complexes with minor or no contribution of the metallacyclopropane structure, despite the fact that chemical shifts of the olefin moiety appear in the aliphatic region [11] …”
Section: α‐Eliminations Cleaving C−c Bondsmentioning
confidence: 99%
“…From a mechanistic point of view, oxidative additions and β‐eliminations are the two most common pathways for transition metal mediated C−C bond cleavage whereas there are still few reports on α‐eliminations [9–11] . For unstrained C−C‐bonds, however, oxidative additions are uncommon, particularly in a catalytic context, and this review will emphasize the use of α‐ and β‐elimination which may be better options for C−C bond cleavage and high‐light work where these mechanistic steps have been shown to operate.…”
Section: Introductionmentioning
confidence: 98%
“…Single crystal X-ray studies were undertaken on 2 a • Et 2 O, 2 b, 3 • 2CH 3 OH and 3' • 1 = 2 CH 3 OH. [20,21] Suitable crystals of 2 a • Et 2 O and 3 • 2CH 3 OH were obtained by vapour diffusion of Et 2 O into a CDCl 3 (for 2 a), slow diffusion of CH 3 OH into a CDCl 3 (for 2 b) or vapour diffusion of Et 2 O into a CH 3 OH (for 3 and 3') solution over several days (Figure 2, Figure 3, Figure 4, and SI). All four structures reveal classic, three-legged, piano stool geometries, with the iridium centres coordinated by an η 5 -Cp* and either two chlorides and a P-monodentate 1 or an anionic P/N amine /Cterdentate 1.…”
Section: Synthesis and Reactivity Of Complexes Withmentioning
confidence: 99%
“…The IrÀ C(30) distance [2.212(8) Å] is slightly longer than observed in known CÀ H activated iridium (III) compounds. [8,18,21] The most remarkable feature of the molecular structures of 3 • 2CH 3 OH and 3' • 1 = 2 CH 3 OH is the unusual η 3 -P/N/C coordination mode of 1, affording an iridacycle with both IrPC 4 (or IrPC 3 N) six-membered and IrC 2 N fourmembered rings. The acute C(30 in accord with formation of a four-membered IrNC 2 ring.…”
Section: Synthesis and Reactivity Of Complexes Withmentioning
confidence: 99%